Debt trap dynamics: The moderating role of convenience, financial literacy, and religiosity in credit card usage - Saeed Siyal; Riaz Ahmad; Shamrez Ali (Journal of Open Innovation: Technology, Market and Complexity)
In the modern age, the card payment business has flourished in Pakistan. Many multinational and national commercial banks have not only introduced debit cards but also many types of credit cards with distinct payment plans, and they are broadly used as financial instruments in consumer financing. The purpose of this research is to identify the distinctive components that cause credit card debt and how Pakistanis are snared into a debt trap by using credit cards. For this purpose, the study examines the effects of credit card usage (CCU), materialism (M), installment plan (IP), convenience (CONV), religiosity (R), and financial literacy (FL) on a dependent variable, debt trap (DT). Furthermore, the moderation impacts of R, FL, and CONV are tested too. The quantitative research approach and cross-sectional research design were applied. The data was collected from 297 credit card users by using a convenience sampling technique that shows a 79.2 % response rate. The Partial Least Square (PLS)-Structural Equation Modeling (SEM) technique was employed for data analysis. The Partial Least Square (PLS)-Structural Equation Modeling (SEM) direct effect has shown that CCU, M, IP, CONV, and R have a significant relationship with DT while FL has an insignificant relationship with the DP. In other words, the indirect effect has shown that FL is not significantly moderate in the relationship between R and DT. Likely, CONV does not significantly moderate the relationship between CCU and DP, however; other indirect effects show a significant moderated relationship of all other independent and dependent variables. Most of the moderating effects are supported, therefore the moderating effects are significant contributions. The study findings could help banks and regulatory bodies in launching these types of credit cards which are under shariah complaints about captivating the users to use the credit card without any fear. This research is a pioneer study in the context of the Pakistan banking sector along with three moderators, religiosity, financial literacy, and convenience. Based on the findings of this research, policymakers and financial institutions in Pakistan should consider introducing Shariah-compliant credit cards that align with users' religious beliefs, while promoting financial literacy programs to better educate consumers on responsible credit card usage and debt management, thus preventing them from falling into debt traps.